PENINGKATAN KEMAMPUAN MENGIDENTIFIKASI UNSUR INTRINSIK DRAMA MELALUI MEDIA FILM PENDEK DENGAN METODE PJJ - Kusumawati, Ira (Jurnal Edukasi Khatulistiwa : Pembelajaran Bahasa dan Sastra Indonesia, 2021)
AbstractThe purpose of this study was to describe the planning, implementation, and evaluation of learning to identify the intrinsic elements of drama through the PJJ method in class XI MIPA 2 SMAN 7 Pontianak by taking actions using short film media. This study uses a qualitative descriptive method and the form of CAR research refers to the Arikunto and Sugiyono model. The results showed that the first cycle of learning planning reached 78 with a good predicate and increased in the second cycle to 88 with a very good predicate. The teacher's performance in the implementation of the first cycle of learning obtained a score of 79 with a good predicate then an increase in the second cycle with a value of 91 with a very good predicate. The results of the evaluation of the first cycle, the average grade of 80.00 with a percentage of completeness of 81.08% in the second cycle there was an increase in the average grade of 93.24 with a percentage of completeness of 91.89%. There was an increase in the ability to identify the intrinsic elements of drama through short films using the PJJ method for students of class XI MIPA 2 SMAN 7 Pontianak.